The role of internal feedbacks in shifting deep lake mixing regimes under a warming climate. (26th March 2021) - Mesman, Jorrit P.; Stelzer, Julio A. A.; Dakos, Vasilis; Goyette, Stéphane; Jones, Ian D.; Kasparian, Jérôme; McGinnis, Daniel F.; Ibelings, Bas W.
Abstract: Climate warming is causing changes in the physics of deep lakes, such as longer summer stratification, increased water column stability, reduced ice cover, and a shallower depth of winter overturns. An ultimate consequence of warming would be a transition to a different mixing regime. Here we investigate the role of physical, chemical, and biological feedback mechanisms that unfold during a shift in mixing regime, and whether these feedbacks could prompt and stabilise the new regime. Although climate, interannual temperature variation, and lake morphometry are the main determinants of a mixing regime, when climate change causes shifts in mixing regime, internal feedback mechanisms may gain in importance and modify lake ecosystem functioning. We review the role of these feedbacks in three mixing regime shifts: from polymictic to seasonally stratified, from dimictic to monomictic, and from holomictic to oligomictic or meromictic. Polymictic lakes of intermediate depth ( c . 3–10 m mean depth) could experience seasonal stratification if a stratification event triggers phytoplankton blooms or dissolved organic matter release, reducing transparency and therefore further heating the surface layer. However, this feedback is only likely to have influence in small and clear lakes, it would be easily disturbed by weather conditions, and the resulting stratified state does not remain stable in the long term, as stratification is lost in winter. The ice‐albedo feedback might cause an accelerated shift from ice‐covered (dimictic) to ice‐free (monomictic) winters in sufficiently deep (mean depth 50 m or more) lakes, where temperature memory is carried over from one winter to the next. Nevertheless, there is an ongoing debate into whether this process can persist during natural weather variations and overcome self‐stabilising mechanisms such as thermal insulation by snow. The majority of studies suggest that a gradual transition from dimictic to monomictic is more likely than an abrupt transition. A shift from a holomictic to a meromictic regime can occur if anoxia is triggered by incomplete mixing and an increase in deep‐water density—through the accumulation of solutes—exceeds a density decrease by hypolimnetic warming. A shift to meromixis would strongly alter the biology of a lake and might be difficult to reverse. If solutes accumulate only minimally in the hypolimnion, an oligomictic regime is formed, in which years with complete and incomplete mixing alternate. Understanding the importance of feedback mechanisms and the role of biogeochemistry when lakes shift in mixing regime could lead to a better understanding of how climate change affects lake ecosystems.